Activin-A urine levels correlate with radiological patterns in preterm infants complicated by intraventricular hemorrhage - Giuseppe Lapergola; Giorgia Gasparroni; Alessandro Graziosi; Darek Gruzfeld; Bashir Moataza; Hanna Aboulgar; Hala Mufeed; Iman Iskander; Giovanni Livolti; Fabio Galvano; Gabriella Levantini; Ebe D’Adamo; et al. (Italian Journal of Pediatrics)
Abstract Background To validate the role of Activin A in the early diagnosis and prognosis of preterm newborns at risk for intraventricular hemorrhage and neurological sequelae by means of cerebral ultrasound and magnetic resonance imaging (MRI), currently considered standard of care procedures. Methods We conducted an observational case–control study in 46 preterm newborns, 23 with intraventricular hemorrhage (IVH group) and 23 controls matched for gestational age. Standard clinical, laboratory, cerebral ultrasound monitoring procedures and Activin A urine measurement were performed at four time-points (first void, 24, 48, 96 h) after birth. Cerebral MRI was performed at 40–42 weeks of corrected gestational age. Results Elevated (P < 0.001, for all) Activin A levels were observed in the IVH group at all monitoring time-point. Activin A correlated (P < 0.05, for all) with intraventricular hemorrhage grade on cerebral ultrasound. At the cut-off of 0.08 pg/mL Activin A at 48-h achieved the best sensitivity, specificity, positive/negative predictive values as early predictor of an abnormal MRI pattern (area under the curve: 0.93). Conclusions The present data showing a correlation among Activin A, cerebral ultrasound and MRI provide further support to Activin A inclusion in clinical daily management of cases at risk for intraventricular hemorrhage and adverse neurological outcome.